Rilwanu Lukman : oiling the system - Nzekwu, Obiora (Lagos : Malthouse Press Limited, 1988)
The book is a serious academic analysis and an assessment of Lukman's performance in the oil industry and his personal views about certain issues in connection with the petroleum industry.
Includes bibliographical references and index.
rpm 22/01/2019
Loans
Keywords: Lukman, Rilwanu; Petroleum industry and trade